Association of Advance Collegiate Schools of Business (AACSB) briefing - UiTM, AAGBS (Arshad Ayub Graduate Business School (AAGBS), 2024)
Arshad Ayub Graduate Business School (AAGBS) UiTM Shah Alam hosted a pivotal AACSB briefing, designed to prepare for the upcoming PRT Chair Visit scheduled from September 2 to 5, 2024. This important session aimed to provide insights into the accreditation process and the standards set by the AACSB. The briefing attracted a diverse group of nine Program Coordinators and Heads of Postgraduate Studies from across the nation, representing the campuses of Johor, Melaka, Perak, Penang, Kedah, Terengganu, Kelantan, Sabah, and Sarawak. Their collective expertise and participation underscored the collaborative spirit essential for achieving AACSB accreditation. Facilitated by the esteemed Assoc. Prof. Dr. Hadijah Iberahim, Head of the Quality and Accreditation Unit at AAGBS UiTM Shah Alam, the seminar was an engaging and informative experience, equipping attendees with the knowledge and strategies necessary to excel in the accreditation journey. As the school prepares for this significant event, the commitment to maintaining the highest standards of quality and excellence in business education remains at the forefront.